2021
DOI: 10.1002/ab.21996
|View full text |Cite
|
Sign up to set email alerts
|

An empirically based power primer for laboratory aggression research

Abstract: Recent reviews suggest that, like much of the psychological literature, research studies using laboratory aggression paradigms tend to be underpowered to reliably locate commonly observed effect sizes (e.g., r = ~.10–.20, Cohen's d = ~0.20–0.40). In an effort to counter this trend, we provide a “power primer” that laboratory aggression researchers can use as a resource when planning studies using this methodology. Using simulation‐based power analyses and effect size estimates derived from recent literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The studies were quite similar, the samples were drawn from the same population in consecutive academic years, and the self-report measures have demonstrated utility in both virtual and in-lab administration. Importantly, it has become increasingly apparent that betweenparticipant interactions, such as those we model here, require far more statistical power than researchers, such as us, previously thought (e.g., Hyatt et al, 2022)…”
Section: Present Studymentioning
confidence: 84%
See 1 more Smart Citation
“…The studies were quite similar, the samples were drawn from the same population in consecutive academic years, and the self-report measures have demonstrated utility in both virtual and in-lab administration. Importantly, it has become increasingly apparent that betweenparticipant interactions, such as those we model here, require far more statistical power than researchers, such as us, previously thought (e.g., Hyatt et al, 2022)…”
Section: Present Studymentioning
confidence: 84%
“…Additionally, the results of Study 2 are likely underpowered to detect substantial moderating effects of the audio induction. Future investigations should utilize larger samples to ensure adequate power based on a priori power analysis (Hyatt et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The studies were quite similar, the samples were drawn from the same population in consecutive academic years, and the self-report measures have demonstrated utility in both virtual and in-lab administration. Importantly, it has become increasingly apparent that between-participant interactions, such as those we model here, require far more statistical power than researchers, such as us, previously thought (e.g., Hyatt et al, 2022) 2. Notably, the final sample of participants consisted of a majority of non-White undergraduate students, which is representative of the larger undergraduate population at the university.…”
Section: Present Studymentioning
confidence: 84%
“…Similarly, Study 2 included a brief audio induction, which may not Additionally, the results of Study 2 are likely underpowered to detect substantial moderating effects of the audio induction. Future investigations should utilize larger samples to ensure adequate power based on a priori power analysis (Hyatt et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Though we have focused on psychopathy trait-by-trait interactions, many of the difficulties in detecting these interactions generalize to other personality disorder research scenarios. For example, Hyatt et al (2021) examined power to detect interactions in laboratory aggression research, where researchers frequently examine how experimental condition, a factor with reliability of 1.0, moderates the impact of personality pathology on aggression (Vize et al, 2021; West et al, 2021). Hyatt et al (2021) found that even with interaction effect sizes that are double the size of those typically found in the literature, adequate power (.80) would require sample sizes of at least N = 1,000.…”
Section: Discussionmentioning
confidence: 99%